Analisis Strategi Pemasaran Melalui Media Sosial Dalam Meningkatkan Volume Penjualan Produk Garifi KAMUMU LISNA di Desa Lolomoyo Kecamatan Gunungsitoli Barat - Wiwi Jaya Setia Halawa; Eduar baene; Idarni Harefa; Yupiter Mendrofa (Visi Sosial Humaniora, 2025)
Lack of professional skills in optimal use of E-commerce is a challenge for small and medium enterprises Garifi Kamumu Lisna in increasing product sales volume widely. This study uses a qualitative descriptive approach with qualitative types, data obtained through interviews, observations, and documentation and analyzed using the Miles and Huberman data analysis model approach. The results of the study indicate that Garifi Kamumu Lisna has utilized some social media platforms such as Facebook and WhatsApp to reach a wider market. This strategy is supported by the presentation of product photos that are considered quite attractive, informative descriptions, and quite active interactions with customers through direct messages and comment replies. However, the implementation of this strategy faces obstacles in the form of limited skills in digital marketing by employees, inadequate access to technology, and unstable internet networks. To overcome these challenges, Garifi Kamumu Lisna focuses on developing employee digital skills and adapting to local technological conditions. Overall, the marketing strategy implemented includes important elements such as utilizing social media, strengthening brand image, using quality visual content, and providing discounts and live streaming to increase consumer loyalty. This research contributes to the development of digital marketing practices among small and medium enterprises, especially in maximizing the potential of E-commerce despite resource limitations.